Analysis of Financial Self Efficacy Mediating The Influence of Financial Literacy, Financial Attitude on Financial Management Behavior in Waserda MSMEs in Pangkalan Lesung District - Suryadi, Nanda; Allyah, Nova Nur (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This research is based on the increase in MSMEs actors in Pangkalan Lesung District, especially Waserda MSMEs, which has triggered the government's attention to the sustainability of their businesses. Where for the business continuity of MSMEs, good financial management behavior is required from the business actors. This research aims to see the influence of financial literacy, financial attitudes and financial self-efficacy on the financial management behavior of Waserda MSMEs in Pangkalan Lesung District with financial self-efficacy as a mediating variable. This research design is quantitative research. The data used is primary data. The data collection method uses a questionnaire. The sampling technique uses a probability sampling technique using simple random sampling and the sample size is 85 respondents. Data was processed using the Smart PLS version 4 model for measurement model evaluation tests, structural model evaluation and hypothesis testing. The results of the t test research show that financial literacy, financial attitudes and financial self-efficacy have a significant effect on financial management behavior. And financial self-efficacy as a mediator can mediate financial literacy, financial attitudes towards financial management behavior.